ULTRASONIC-ASSISTED DRYING AND INTERMITTENT DRYING: A MODELING STUDY USING THE REACTION ENGINEERING APPROACH (REA) - Aditya Putranto (Research Report - Engineering Science, 2013)
Drying is a simultaneous heat and mass transfer process which involves significantenergy consumption. For sustainable processing practice, ultrasonic-assisted drying is oftenimplemented. In order to assist in process design and optimization, a physically-meaningfuldrying model is useful. The REA (reaction engineering approach), which has been shown tobe accurate to model several challenging drying cases, is implemented here to model theultrasonic-assisted drying with various intensities. The relative activation energy (ΔEv,b)generated from one accurate drying experiment is used to model the ultrasound-assisteddrying with various intensities. The results of modeling match very well with theexperimental data. The REA is accurate to model the ultrasonic-assisted drying. Themechanisms of ultrasonic-assisted drying can be explained well by the REA. A landmark forprocess intensification of drying process has been set up by the REA. The model can bereadily adopted in industrial settings for process design and optimization.